Hydrological Evaluation of Streamflow Drought Index Method for Different Time Scales: A Case Study of Arsuz Plain, Turkey - Evren TURHAN; Buse Duyan Çulha; Serin Değerli (Doğal Afetler ve Çevre Dergisi)
Drought has been among the priority issues for a long time because of its effects that vary depending on duration and severity. Hydrological drought can be explained as the decrease in clean water resources caused by climate change. In this paper, Arsuz Plain, one of the agricultural protected area in the Asi River Basin, was selected as the case study for the hydrological drought analysis. Firstly, discharge-time and flow duration curves (FDC) were created by using monthly average discharge data between the years of 1990 and 2015 which were obtained from three different Flow Observation Stations (FOSs) (numbered D19A021, D19A022 and D19A023), located close to each other. With the help of these data, Streamflow Drought Index (SDI) values were calculated for different time scales such as 3, 6 and 12 months. Consequently, it has been seen that all three stations have similar results in terms of the peak flow rate values excluding a few periods. As of 2000, it has been observed that Extreme Drought and Extremely Wet periods have started to occur in the basin for these stations. While the most wet period began between the years 2009 and 2010, the driest period was 2014. Considering the course of the drought event in different time scales, it can be concluded that the number of dry periods has increased in recent years.